Handover among multidisciplines in obstetrics - Pace, Julie (My University, 2015)
Background: Communication failures during handover has long been noted as a threat to patient safety.1 Breakdown in communication among health professionals is reported to account for up to 85% of hospital sentinel events.1 Lack of formal structure and training in handover methods 53 as well as modes of communication including nonverbal behaviors 59 have been reported to affect the quality of information exchange in handovers. 59 The objective of this mixed methods study is to conduct a detailed analysis of handover content among physicians and among nurses on a Birthing Unit and to examine communication processes within these groups in order to identify gaps in the process. This may provide a basis for future development of standardized approaches and training efforts. Methods: A convergent, parallel mixed methodology was used. The sample in this study comprises the nurses and medical obstetrical team in a hospital Birthing Unit in Hamilton Ontario. Phase one of the study involved initial observations of handover, performing a Delphi to gain consensus on handover content and creating a handover assessment tool. Phase two involved reliability testing of the tool and in phase three, twenty five paired nurse to nurse compared to medical handovers were video recorded, scored and correlated to participant questionnaires. Results: Gaps in handover content were identified; the nurses achieved a mean score of 10.24 items compared to physicians mean score of 9.02 (correlation 0.582, p <0.01). This showed statistically significant differences in the items mentioned among the two groups iii (t = 13.2, p < 0.001). Nonverbal behaviors noted during handover observations revealed inconsistencies in conveying information, within and between the two groups. The findings of this study contribute to a better understanding of handover gaps, has implications to other health team practices and highlights the need for standardized processes, training and policy development.
Handover among multidisciplines in obstetrics: a mixed methods study of content and communication process
Keywords: handover, obstetrics; multidiscipline